2012
DOI: 10.1007/s00418-012-0960-1
|View full text |Cite
|
Sign up to set email alerts
|

Gsdma3 is a new factor needed for TNF-α-mediated apoptosis signal pathway in mouse skin keratinocytes

Abstract: Gsdma3, a newly found gene, is expressed restrictedly in mouse skin keratinocytes and gastrointestinal tract. But until now, there is little information on the regulation and the function of Gsdma3 in skin keratinocytes. In our previous study, we found that Gsdma3 mutation resulted in a decrease in catagen-associated apoptosis of hair follicle keratinocytes. Apoptosis of skin keratinocytes is strictly regulated by a series of signal pathways, among of which, tumor necrosis factor (TNF)-α-induced signal pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…TNF-α induces caspase 3 activation which leads to subsequent cellular damage including endothelial barrier dysfunction [29, 30]. We first assessed whether HDAC6 inhibition can block caspase-3 activation in lung endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α induces caspase 3 activation which leads to subsequent cellular damage including endothelial barrier dysfunction [29, 30]. We first assessed whether HDAC6 inhibition can block caspase-3 activation in lung endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…They share similar phenotypes, including cicatricial alopecia accompanied by hair follicle differentiation defects, atrophy of the stratum granulosum (SG) and hyperkeratosis [17][18][19][20][21][22][23]. Previous reports suggest that Gsdma3 is associated with hair follicle development [21,24], tumour necrosis factor (TNF)α-induced apoptosis [25], skin inflammation [26,27] and immune-mediated destruction of bulge stem cells [23]. However, the physiological function of Gsdma3 is still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Qin et al have reported that inhibition of cell apoptosis significantly improves heart function in myocardial infarction rabbits [12]. In particular, TNF- α /caspase-3-mediated apoptosis is considered the main apoptotic pathway in heart failure (HF) [13]. Therefore, in vivo detection of apoptosis may not only prove clinically useful in diagnosis and prognosis but also indicate that the TNF- α /caspase-3 pathway is potential therapeutic target [14].…”
Section: Introductionmentioning
confidence: 99%